Literatura e sociedade em Chiquinho: correspondências entre intelectualidade e caboverdianidade - Hofmã, Patrícia (2019)
The present research intends to demonstrate the relation between the Cape Verdean intellectuality and Cape Verdianity. Also intends to confront the contents of theoretical texts with the novel Chiquinho (1947), by the writer Baltasar Lopes, in order to verify possible contours or features that unify, in a particular way, a Cape Verdean identity as a legitimizing element of a project idealized by the “claridosa” generation, emphasizing the relations established between the process of construction of the national identity and the Cape Verdean intellectuality. The novel under analysis, was first published in 1947 and it was considered as the first truly Cape Verdean novel, becoming part of Cape Verde's literary formation process. The narrative, divided into three parts, can be classified as a Bildungsroman text, because it presents the trajectory of the protagonist Chiquinho, from his childhood, youth, until his adulthood. The novel covers aspects of the archipelago’s reality, as the harsh reality of droughts and hunger that affects the population, also its cultural peculiarities, such as oral narratives, the Creole language and the “mornas”. In addition, the text also presents the issue of evasionism and intellectual engagement as components of the identity of Cape Verdean individuals. The theoretical basis include a discussion of the aspects of settlement and formation of Cape Verde society, the concept of "intellectual", based on authors as Gramsci, Edward Said and Alfonso Berardinelli, and a synthetic route for the formation of Cape Verdean literature.